Determinants Of Digital Advertising Adoption Among Smes In Malaysia - Wan Nur Fazni Wan Mohamad Nazarie; Mohammad Tahir Zainuddin; Sofyan Rofi; Muhammad Naqib Bin Nurul Akhmal (Universal Publishers, 2026)
Purpose: This study aims to examine the determinants influencing small and medium-sized enterprises’ (SMEs) intention to adopt digital advertising in Malaysia, using the Theory of Planned Behaviour (TPB) as the theoretical framework. Specifically, it examines the impact of economic benefits, perceived usefulness, brand awareness, and return on investment (ROI) on adoption intention. Design/methodology/approach: A quantitative research design was utilized, employing a cross-sectional survey disseminated online to a purposive sample of 496 small and mediumsized enterprise owners and managers throughout Malaysia. The data were examined utilizing SPSS, incorporating descriptive statistics, reliability analysis, Pearson’s correlation, and multiple regression to evaluate the offered hypotheses. Findings: The result shows that all four variables positively impact SMEs’ intention to adopt digital advertising. Economic benefit and return on investment (ROI) emerged as the most significant factors, demonstrating that financial considerations predominantly influence the adoption of digital advertising, although perceived usefulness and brand awareness also play substantial roles. Research limitations/implications: The study's cross-sectional design restricts causal inference, and the findings are exclusively derived from Malaysian SMEs, which may diminish generalizability. The adoption patterns and cultural differences that are evolving could be captured through longitudinal and comparative cross-country research in the future. Practical implications: The findings give useful information to owners of small and mediumsized businesses and digital platform providers. Originality/value: This study extends the theory of Planned Behaviour by integrating Return on Investment (ROI) and brand awareness into the framework, offering empirical evidence from the context of an emerging economy. It contributes to the limited body of research on SME digital advertising adoption in Southeast Asia for enhancing SME digital transformation strategies